Assessment of pulmonary functions with spirometry method in hepatic impairment patients (Annals of Medical Research, 2021)
Aim: In this study, it has been aimed to investigate whether there is a relationship between pulmonary functions measured by spirometry and hepatic impairment tables. This may contribute to a better understanding of the mechanisms of liver pathophysiology which hasn’t been fully understood.Materials and Methods: This study is a randomized controlled prospective trial. 39-63 years of age, 19 male and 9 female, a total of 28 patients diagnosed with liver failure, with 15 male and 17 female, a total of 32 healthy volunteers with similar social characteristics were studied. All of the participants’ pulmonary parameters (FEV1, FVC, FEV1/FVC, PEF, FEF25-75%, FEF25%, FEF50%, FEF75%, PIF, VC, MVV) were performed by pulmonary function tests (PFT). Groups’ data have been analyzed statistically. The significance level was considered as p0.05.Results: In hepatic impairment patients, there was no significant difference in terms of the expected percentage values of PFT parameters that indicate obstruction. Weak restriction in 8 cases, moderate restriction in 9 cases and severe restriction in 4 cases were diagnosed. PFT parameters of patients with mid-level and refractory ascites were found to be significantly lower compared with those without ascites (FEV1: p=0.009; FVC: p=0.010; VC: p=0.008). There was no remarkable correlation between AST, ALT, ALP, GGT levels and PFT parameters of patients as with ascites status.Conclusion: Ascites that can frequently coexist with chronic liver disease cases, may cause restrictive type pulmonary dysfunctions in PFT by creating mechanical pressure. But also, there is no correlation between the ascites status or PFT diagnoses and liver function tests.
Keywords: Ascites; hepatic impairment; pulmonary function tests; spirometry